Epigenetics Regulates Antitumor Immunity in Melanoma - Chen, Yuhan; Yi, Xiuli; Sun, Ningyue; Guo, Weinan; Li, Chunying (Frontiers in Immunology, 2022)
Melanoma is the most malignant skin cancer that originates from epidermal melanocytes, with increasing worldwide incidence. The escape of immune surveillance is a hallmark of tumor, which is manifested by the imbalance between the enhanced immune evasion of tumor cells and the impaired anti-tumor capacity of infiltrating immune cells. According to this notion, the invigoration of the exhausted immune cells by immune checkpoint blockades has gained encouraging outcome in eliminating tumor cells and significantly prolonged the survival of patients, particularly in melanoma. Epigenetics is a pivotal non-genomic modulatory paradigm referring to heritable changes in gene expression without altering genome sequence, including DNA methylation, histone modification, non-coding RNAs, and m6A RNA methylation. Accumulating evidence has demonstrated how the dysregulation of epigenetics regulates multiple biological behaviors of tumor cells and contributes to the carcinogenesis and tumor progression in melanoma. Nevertheless, the linkage between epigenetics and anti-tumor immunity, as well as its implication in melanoma immunotherapy, remains elusive. In this review, we first introduce the epidemiology, clinical characteristics and therapeutic innovations of melanoma. Then, tumor microenvironment and the functions of different types of infiltrating immune cells are discussed, with the emphasis on their involvement in anti-tumor immunity in melanoma. Subsequently, we systemically summarize the linkage between epigenetics and anti-tumor immunity in melanoma, from the perspective of distinct paradigms of epigenetics. Ultimately, the progression of the clinical trials regarding epigenetics-based melanoma immunotherapy is introduced.